Analisis Ketersediaan Koleksi Buku Perpustakaan Menggunakan Bibliometrik - Yasmidar, Nicky; Aliwijaya, Araf (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Books are one of the main collections served by libraries. There are books that are often used as reference material, but there are also books that are used sparingly. On the other hand, there are books that are used as references by users that have not been provided by the library. This research aims to see the availability of book collections based on the number of student thesis citations. This research uses a quantitative approach with bibliometric methods. The main data for this research are citations from student theses from the Universitas Medan Area communication science study program for 2020-2022. The data collected is in the form of a list of citations contained in the thesis. Search, collection and filtering of thesis citation data was carried out. After filtering, the data was tabulated using Ms. Excel will then be compared with the availability of the UMA Library collection via the library's OPAC. The number of book citations contained in communication science students' theses for 2020-2022 in the UMA repository has reached 1,928. Measurements were carried out to evaluate the availability of book collections in the library and provide 44 recommendations for book procurement as improvement steps. Bibliometrics can be used as a tool to measure the usefulness of collections and provide recommendations for the procurement of library collections. However, research involving more research report and study program is expected to produce more comprehensive recommendations.